Patterns in life quality changes of Irkutsk city’s inhabitants according to SF-36 questionnaire - T. A. Roy (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Actuality. At the moment, one of the current trends in medicine and sociology is the study of life quality in population. The motivation for this study was the lack of population-based studies on life quality assessment for adult population conducted in Irkutsk, taking into account the individual characteristics of all age groups with questionnaire SF-36. Purpose. To evaluate standard criteria for Irkutsk adult population's life standard in terms of the age and gender by means of the standard questionnaire SF-36. Materials and methods. The article represents the interview results received from 579 Irkutsk dwellers at the age of 18-85. The Russian version of SF-36 Questionnaire has been used for the present research. The criteria were estimated according to 8 scales. The levels of the respondents' physical well-being, socio-environmental adaptation, psycho-emotional changes and viability were specified. Moreover, the respondents' clinical-anamnestic status including complaints, anamnestic evidences for somatic pathology and earlier surgical interventions were evaluated as well. The received data were processed by Statistica 6.0 software with the use of nonparametric and multiple factor analysis. Results. The results determine the levels of physical functioning, social adaptation, psycho-emotional changes and the viability of Irkutsk residents of different age, gender and socio-professional groups. Conclusions. The presence of comorbidity in varying degrees affected the quality of life.